2022
DOI: 10.1002/cbin.11889
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA FGD5‐AS1 potentiates autophagy‐associated doxorubicin resistance by regulating the miR‐154‐5p/WNT5A axis in osteosarcoma

Abstract: Osteosarcoma is prevalent in children and adolescent. The oncogenic function of long‐chain noncoding RNA (lncRNA) FGD5 antisense RNA 1 (FGD5‐AS1) has been reported. However, the function of FGD5‐AS1 in doxorubicin‐resistance in osteosarcoma remains to be illucidated. Quantitative real‐time PCR (qRT‐PCR) and western blot analysis (WB) were used to measure the expression of FGD5‐AS1, miR‐154‐5p, WNT5A and autophagy proteins. MTT assay was used to assess cell viability and transwell assay was performed to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…After DOX exposure, regulation of miR‐142 and downstream target genes ULK1 , ATG4A , and ATG5 promotes autophagy index LC3II and Beclin1 protein levels and reduces P62 protein levels by activating autophagy and increasing Sox2OT‐V7 levels, thus encouraging autophagy and the chemotherapy resistance brought by DOX (Zhu, Yuan, et al, 2020). Moreover, WNT5A, which is a noncanonical Wnt pathway regulator, was increased by FGD5‐AS1 to facilitate autophagy, resulting more sensitivity to DOX by sponging miR‐154‐5p in OS cells (Fei et al, 2022). Studies have found that ODRUL is more significantly expressed in DOX‐resistant OS cells than OS cells.…”
Section: Lncrnas Associated With Drug Resistance In Osmentioning
confidence: 99%
“…After DOX exposure, regulation of miR‐142 and downstream target genes ULK1 , ATG4A , and ATG5 promotes autophagy index LC3II and Beclin1 protein levels and reduces P62 protein levels by activating autophagy and increasing Sox2OT‐V7 levels, thus encouraging autophagy and the chemotherapy resistance brought by DOX (Zhu, Yuan, et al, 2020). Moreover, WNT5A, which is a noncanonical Wnt pathway regulator, was increased by FGD5‐AS1 to facilitate autophagy, resulting more sensitivity to DOX by sponging miR‐154‐5p in OS cells (Fei et al, 2022). Studies have found that ODRUL is more significantly expressed in DOX‐resistant OS cells than OS cells.…”
Section: Lncrnas Associated With Drug Resistance In Osmentioning
confidence: 99%
“…Doxorubicin (DOX) is an antibiotic chemotherapeutic agent which inhibits proliferation and induces apoptosis by blocking topoisomerase II activity and causing DNA breaks ( Ashrafizaveh et al, 2021 ). lncRNA-mediated autophagy is closely in connection with DOX resistance in cancer cells, according to a growing number of studies ( Guçlu et al, 2021 ; Fei et al, 2022 ). Among triple-negative breast cancer (TNBC), a new type of nanodrug delivery system based on CL4-modified exosomes was able to deliver the siRNA of lnc-DARS-AS1 to TNBC cells, and silencing of DARS-AS1 by this delivery system increased DOX sensitivity of BC cells by suppressing autophagy induced by the TGF-β/Smad3 axis ( Liu et al, 2023 ).…”
Section: Lncrna-mediated Autophagy In Cancersmentioning
confidence: 99%
“…Erlotinib induced autophagy to promote erlotinib resistance via 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (PFKFB3) in NSCLCs [ 122 ]. Wingless-related integration site 5A (Wnt5A)-induced autophagy mediated doxorubicin resistance in osteosarcoma cells [ 123 ]. The inhibition of autophagy sensitized glioblastoma cells to Src tyrosine kinase inhibitors such as Si306 and pro-Si306 [ 124 ].…”
Section: Role Of Autophagy In Senescencementioning
confidence: 99%